Gunboat Diplomacy in Natuna Waters from 2010-2020: Indonesia’s Deterrence in South China Sea Conflict - Anugerah Akbar Maulana (Laboratorium Hubungan Internasional, FISIP, Universitas Jenderal Soedirman, 2022)
Abstract SCS conflict comprises a substantial threat to Indonesia as China’s nine-dash line overlaps with Indonesia’s Exclusive Economic Zone EEZ in Natuna waters. The spillover of the conflict was exposed through China’s incursions in Natuna waters from 2010 to 2020 as China regard it has the right to carry out activities in several areas of Natuna waters that are considered as part of maritime territorial violations for Indonesia. Indonesia deploys the capabilities of its naval forces’ in Natuna waters in response to China’s incursions in which this phenomenon could be regarded as gunboat diplomacy. This study aimed to reveal the efficacy of Indonesia's gunboat diplomacy to deter China's incursions in Natuna Waters. Through the qualitative method, official documents and relevant literature will be analyzed to answer the study's objective. Employing gunboat diplomacy and deterrence as the conceptual framework, this study discerns that Indonesian naval forces become the forefront instrument as gunboat diplomacy in deterring China's assertiveness in SCS dispute, which led to the incursions over Indonesia maritime territory in Natuna. This study discovered that Indonesia's gunboat diplomacy leveraged as the purposeful forces and expressive force in which the warship managed as the media of diplomacy that altered China's vessels' behaviour over the incursions in Natuna waters and enabled Indonesia naval force fruitful to crackdown China's incursions in particular point of the occasion. However, gunboat diplomacy as Indonesia's deterrence means has not thoroughly delivered a deterrent effect to China since Chinese vessels' activities still recurred in Natuna waters at the latest 2020. Abstrak Konflik Laut Tiongkok Selatan (LTS) memuat ancaman bagi Indonesia karena sembilan garis putus-putus Tiongkok tumpang tindih dengan Zona Ekonomi Ekslusif Indonesia (ZEE) di perairan Natuna. Limpahan konflik tersebut terpapar pada serbuan Tiongkok di perairan Natuna sejak tahun 2010 hingga 2020 dimana Tiongkok menganggap memiliki hak untuk beraktivitas di beberapa area di perairan Natuna, sedangkan hal tersebut dianggap sebagai pelanggaran wilayah maritim bagi Indonesia. Indonesia mengerahkan kemampuan angkatan lautnya di perairan Natuna sebagai tanggapan atas serbuan Tiongkok di mana fenomena ini dapat dianggap sebagai diplomasi kapal perang. Penelitian ini bertujuan untuk mengungkap seberapa ampuh diplomasi kapal perang Indonesia untuk menangkal serbuan Tiongkok di perairan Natuna. Melalui metode kualitatif, dokumen resmi dan literatur yang relevan akan di analisa untuk menjawab tujuan penelitian. Menggunakan diplomasi kapal perang dan deterensi sebagai kerangka konseptual, penelitian ini melihat bahwa kekuatan angkatan laut menjadi instrumen terdepan sebagai diplomasi kapal perang untuk menangkal perilaku asertif Tiongkok di konflik Laut Tiongkok Selatan (LTS) yang menyebabkan Tiongkok menyerbu wilayah perairan Indonesia di Natuna. Penelitian ini menemukan bahwa diplomasi kapal perang Indonesia digunakan sebagai kekuatan yang bertujuan dan kekuatan ekspresif di mana kapal perang dikelola sebagai media diplomasi untuk mengubah perilaku kapal-kapal Tiongkok pada penyerbuan di perairan Natuna yang memungkinkan kekuatan angkatan laut Indonesia dapat menindak serbuan Tiongkok di perairan Natuna pada titik waktu tertentu. Namun, diplomasi kapal perang sebagai sarana deterensi Indonesia belum dapat memberikan efek jera kepada Tiongkok secara menyeluruh karena aktivitas kapal Tiongkok di perairan Natuna masih terjadi paling terbaru pada tahun 2020.